ANALISIS DETERMINAN PERMINTAAN MASYARAKAT TERHADAP JASA PENGIRIMAN PAKET PADA PT. POS INDONESIA (PERSERO) SUMBAWA BESAR - Kartini, Erni; Suprianto, S (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to know the determinants of public demand for package delivery services at PT. Pos Indonesia (Persero) Sumbawa Besar, namely shipping rates and public income. The type of data used was quantitative data obtained directly from primary sources using a research instrument in the form of a questionnaire. The sample that will be used as respondents in this study was all users of package delivery services at PT. Pos Indonesia (Persero) Sumbawa Besar, totaling 96 people. The selection of respondents was carried out using non-probability sampling techniques with the simple random sampling method. Data analysis tools were performed using multiple linear regression analysis techniques, t test, F test, and the coefficient of determination (R2) test. The results of this study showed that in partially shipping rates had a negative and significant effect on community demand for package delivery services, while community income had a positive and significant effect on community demand for package delivery services at PT. Pos Indonesia (Persero) Sumbawa Besar. In simultaneously, shipping rates and community income had a significant effect on community demand for package delivery services at PT. Pos Indonesia (Persero) Sumbawa Besar. The ability of shipping rates and community income to influence changes on community demand for package delivery services at PT. Pos Indonesia (Persero) Sumbawa Besar was 67.5%, while the remaining of 32.5% was effected by other variables not examined in this study, such as the implementation of marketing mix strategies which include product, place, promotion, price, people, process, and physical evidence.